PELANGGARAN ETIKA PERIKLANAN DALAM IKLAN LUAR GRIYA PEMILU 2024 - Hanifah, Azhar; Hazza, Faishal; Nadia, Khoirunnisa Anna; Junaedi, Fajar (Universitas Muhammadiyah Jakarta, 2024)
Advertising as a form of promotion or as a visual aid in introducing 2024 election candidates to the publik through billboards, posters and several other visual aids. Bawaslu and EPI are the institutions that regulate policies in the campaign leading up to the election so that everything can run smoothly in accordance with applicable regulations. Several election candidates ignored the rules from Bawaslu and EPI in carrying out campaigns using poster advertisements, such as inappropriate placement of posters, excessive number of posters, and several other rules. The method used in this research is descriptive qualitative by understanding a phenomenon that is occurring. The data collection technique used in this research was observation of Griya's external advertisements related to the 2024 election taken from mass media pages. The research results show that even though there are regulations from Bawaslu and EPI in setting rules during the campaign leading up to the 2024 elections, many election candidates do not comply with them properly. The existence of rules that are not obeyed by election candidates has a negative impact on the environment and society, one of which is a vocational school student who had an accident due to a poster on the main road suddenly falling, causing the vocational school student to die.